Dr. Tarek Zahra — Deep Plane Facelift — Kuwait City - Zahra, Tarek (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Tarek Zahra, practicing in Kuwait City, Kuwait. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003107; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; kuwait; kuwait city